Elementos climáticos e internações hospitalares por doenças respiratórias em Uberlândia (MG): perspectivas e desafios nos estudos de clima e saúde - (:unkn) unknown (Universidade Federal de Goiás, 2014)
Since the Federal Constitution in 1988, are "granted "to individuals various social rights, including the right to health. A right which should be guaranteed by the state through measures that ensure the humane treatment of Brazilians, regardless of social class, race or religion. Faced with various transformations and increasingly complex demands of modern society, it is necessary a more accurate understanding of the environmental issues of today. Through this research, it was found that, in Uberlândia (MG), from 2005 to 2011, a total of 26, 934 hospitalizations for respiratory complications. In this research it appears that there is a correlation between the air temperature, relative humidity and human health. The diseases with the highest occurrence is pneumonia (which amounts to more than 45% of total inpatient cases), followed by other diseases of the nose and paranasal sinuses; bronchitis, emphysema; chronic diseases of tonsils; influenza [Flu] and asthma. The correlation of these diseases with the weather elements is evident in the months of March, April, May, June and July, in which are recorded the highest number of admissions for respiratory diseases. During these periods there is the transition from autumn season - winter, which causes significant fluctuations in relative humidity, this happens due to warmer temperatures in the morning and cooler in the day. This problem of moisture can be seen in months like May and June as the atmosphere becomes progressively drier , reaching values below 30% relative humidity. In a general analysis of hospitalizations by age and gender, we have that the maximum and minimum hospitalizations, predominantly children under nine years of age and older as the most affected . Children continue to be the portion of the population most affected by respiratory problems, occupying more than 50% of the cases evaluated. It is important to mention that while there is significant correlation between disease and behavior of temperature and humidity, maximum and minimum admissions should be seen in the composition of totality (holorritmo), since this research does not take into account elements of another kind, as biological, psychological, emotional, and physical aspects in relation to housing (infrastructure , molds, building material), which are crucial for the complete understanding of the system and respiratory morbidity. Become appropriate search these admissions, since these groups of chronic diseases represent today the third leading cause of death in Brazil, second only to cardiovascular disease and cancer . In this sense, it is expected that the results of this work, the government can get conditions to improve health intervention, enabling a reduction in spending and creating more effective public policies vulnerable to the spread of disease areas.
Climate elements and respiratory diseases in hospitalizations in Uberlândia (MG): propsects and challenges in studies of climate and health
Keywords: Elementos climáticos; Doenças respiratórias; Geografia da saúde; Uberlândia; Climatic elements; Respiratory diseases; Geography of health; CIENCIAS HUMANAS::GEOGRAFIA